Impact of school participation on quality of life of Brazilian children with cerebral palsy - Presumido Braccialli, Lígia Maria [UNESP]; Silva, Michelle Zampar [UNESP]; Braccialli, Ana Carla; Sankako, Andréia Naomi [UNESP]; De Cássia Tibério Araújo, Rita [UNESP] (De Gruyter, 2016)
The study aimed to analyze the impact of school participation on quality of life of Brazilian children with cerebral palsy. Participants of the study were primary caregivers of children with CP: 39 caregivers of children not attending regular or special school and 74 caregivers of children attending regular or special school. Children with CP, including males and females, were between 4 and 12 years old. Data collection was carried out through individual interviews and application of the questionnaire Cerebral Palsy Quality of Life Questionnaire for Children CP QOL-Child (4-12 years). There was a significant difference in quality of life between the group of children attending school and the group not attending school for the Functioning Domains (p=0.0014), participation and physical health (p=0.0277) and emotional well-being (p=0.05). The worst score was obtained for the pain and impact of disability domain and impact of disability for both groups. We also found significant difference in the distribution of quality of life between genders. The results indicated that the opportunity to experience school has a positive impact on the quality of life of children with cerebral palsy in relation to functioning, participation and physical health and emotional well-being, regardless of gender and age.
Keywords: cerebral palsy; inclusion; quality of life